Instagram as Media to Enhance Students’ Writing Skill Viewed from Students’ Creativity in State Islamic Institute of Ponorogo - Kaukabilla Alya Parangu; Sulistyowati Sulistyowati (Study Program of Arabic Language Teaching, 2020)
Utilizing Instagram as media in teaching English is a new phenomenon in Education. Naturally, Instagram is a social media that usually used for sharing pictures and videos which is mostly used by the youths. However, it is such a good chance to use something the students are excited about for educational purpose. This research aims to identify whether: 1) Instagram can improve the students’ writing skill; (2) there is an interaction between teaching media and students’ creativity in teaching writing. This research is classified as quasi-experimental study and the subjects of the research were 36 students of Shariah Economics in Economics Faculty in State Islamic Institute of Ponorogo. The data obtained during the research are in qualitative and quantitative forms. The data were acquired by using two instruments; questionnaire and writing test. Questionnaire was used to categorize both students having high or low creativity, and writing test was used to measure their writing skill. The data were, then, analyzed by using Multifactor Analysis of Variance ANOVA and Tukey test. Before conducting the ANOVA, pre-requisite tests such as normality and homogeneity test were conducted. This study finds that: (1) Instagram media is more effective than Powerpoint media to teach writing; (2) There is an interaction between teaching media and students’ creativity in teaching writing. The result of this study implies that Instagram media is an effective media in teaching writing to the second semester students.